Faktor-faktor Budaya Penghambat Penderita Kanker Berobat ke Fasilitas Pengobatan Modern - Sri Meiyenti; Maihasni Maihasni; Aziwarti Aziwarti (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
This article based on research that tries to trace cancer patients who do not want to go to the hospital. Often we hear cancer patients come to the hospital when the condition of the disease is already at an advanced stage. So it's too late to handle. According to data from the Ministry of Health of the Republic of Indonesia, if cancer is treated early it can prevent more than 30 percent death. This study aims to determine the problem of cancer patients' reluctance to go to the hospital in terms of socio-cultural aspects. The method used in this research is a qualitative method. Data collected by observation and in-depth interview techniques. The results showed that the reluctance of cancer patients to go to the hospital was influenced by socio-cultural aspects so it was crucial to determine the choice of treatment for cancer patients. The socio-cultural aspects are cultural knowledge about cancer, belief in traditional medicine, and the influence of relatives and other social environments such as friends and neighbors in health care choices. Relatives, neighbors, and friends recommend traditional treatment. However, with traditional medicine, there are no informants who have recovered from their illnesses. There is actually a disease that is getting worse.